Influence of Islamic Financial Literacy, Religiosity on Interest Customer with Moderation Promotion - Anindya, Aprilia Dwi Marta; Hakim, Luqman (Universitas Negeri Semarang, 2021)
The purpose of this study is to determine the effect of Islamic financial literacy and religiosity on interest in becoming a customer in Islamic banks with promotion as a moderating variable. This research is a quantitative research. The sample used in this study was 100 students of State Universities in Surabaya with a purposive random sampling technique. The questionnaire was used as a data collection technique. While the data analysis technique used descriptive statistics and multiple linear regression. For moderating variables using the MRA test. The results of this study indicate that there is a partial or simultaneous influence between the variable X on the Y variable, while the promotion variable in this study does not moderate the independent and dependent variables. Based on this research, students are expected to be able to apply the knowledge they have acquired by learning about Islamic financial literacy including deepening religious knowledge to be applied in everyday life.